The incidence of rheumatoid arthritis in the UK: comparisons using the 2010 ACR/EULAR classification criteria and the 1987 ACR classification criteria. Results from the Norfolk Arthritis Register - Jennifer Humphreys; Suzanne Verstappen; Kimme L Hyrich; Jacqueline R. Chipping; Tarnya Marshall; Deborah Symmons (2012)
Objectives The development of new classification criteria for rheumatoid arthritis (RA) calls for a re-estimation of RA incidence rates. The objectives of this study were to estimate the age and sex-specific incidence rates (IR) of RA in Norfolk, England using the 2010 American College of Rheumatology (ACR)/European League Against Rheumatism criteria, and to compare those with IRs estimated using the 1987 ACR criteria. Setting The Norfolk Arthritis Register (NOAR), a large primary care inception cohort of patients with inflammatory oligo- and polyarthritis (IP) aged ≥ 16. Methods All patients notified to NOAR from 1990-5 with symptom onset in 1990 were included. The former Norwich Health Authority population was the denominator. Age and sex specific IRs using 1987 and 2010 classification criteria were calculated at baseline visit, annually for the first 3 years and at 5 years. Results 260 patients were notified to NOAR with symptom onset in 1990 and without an alternative diagnosis. IRs applying the 2010 criteria at baseline were 54/100 000 for women and 25/100 000 for men. Age and sex-specific IRs using the 2010 classification criteria at baseline were similar to cumulative IRs applying the 1987 criteria up to 5 years. However, some patients only ever satisfied one set of criteria and a proportion of IA patients (20%) did not satisfy either criteria set over 5 years. Conclusions The 2010 criteria classify similar numbers of patients as having RA at baseline, as the 1987 criteria would have taken up to 5 years to identify.